2013
DOI: 10.17221/529/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of spinach, peas and sweet corn in relation to freezing period

Abstract: Bajčan D., Tomáš J., Uhlířová G., Árvay J., Trebichalský P., Stanovič R., Šimanský V. (2013): Antioxidant potential of spinach, peas, and sweet corn in relation to freezing period. Czech J. Food Sci., 31: 613-618.We evaluated changes in the content of total polyphenols and antioxidant activity of frozen spinach, peas, and sweet corn in relation to the storage period. Total polyphenol content and antioxidant activity in analysed samples were determined by colorimetric methods. Both parameters were analysed in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Similar level of total and reducing sugars and protein content has been reported in sweet corn kernels in some other recent studies (Bajčan et al . ; Nunes et al . ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Similar level of total and reducing sugars and protein content has been reported in sweet corn kernels in some other recent studies (Bajčan et al . ; Nunes et al . ).…”
Section: Resultsmentioning
confidence: 96%
“…In another study where samples were stored at freezing (−18C) temperature, some reductions in these activities were reported (Bajčan et al . ). Phytochemicals, such as phenolics including flavonoids present in different foods, have been reported to scavenge free radicals by getting oxidized and hence have potential to reduce free radicals associated health disorders (Kumar et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years, in the literature authors pay increasing attention to antioxidant compounds, due to their ability to neutralize free radicals (Devasagayam et al, 2004;Gramza-Michałowska and Korczak, 2013;Kuźma et al, 2014;Sarić et al, 2013;Bajčan et al, 2013). It has been found that antioxidants may interfere with oxidation reactions with free radicals, exhibit properties to chelate catalytic metals, as well as scavenge oxygen (Buyukokuroglu et al, 2001).…”
Section: Antioxidant Properties and The Total Polyphenol Contentmentioning
confidence: 99%
“…Bunun yanında gıda, parfüm ve kozmetik gibi birçok sanayi dalında da kullanım alanı bulmaktadırlar [2] Ayrıca bu alanlarda tıbbi bitkilere verilen önem giderek artmaktadır. Son yıllarda araştırmacılar gıda endüstrisinde antimikrobiyal etkileri, serbest radikalleri nötralize etme yeteneği, tatlandırıcı özelliği ve bunun gibi daha birçok farklı etkilerinin olması nedeniyle, stevia (Stevia rebaudiana) üzerinde durmakta ve bu bitki ile ilgili çalışmaları literatüre kazandırmaktadırlar [3,4,5].…”
Section: Introductionunclassified